Senior High School Students' Anxiety towards Language Learning Skills - Male, Hendrikus (JET (Journal of English Teaching), 2018)
AbstractThis study merely aims to investigate Senior High School Students’ language anxiety and also to find out what class obtains the most dominant language anxiety. The respondents were administered a set of questionnaire and interview which was adapted from Muhaisen and Al-Haq (2012) The result of data analysis showed that the most dominant of the students’ anxiety were found in speaking followed by reading, writing and listening in their language learning process. It is highly recommended that the teachers be more creative in making the class atmosphere to be more fun and relaxing in teaching the language skills so that the students are more encouraged to learn the language.Keywords: language anxiety, senior high school students, language learning process